FARMERS' KNOWLEDGE ON REASONS NOT TO USE RICE STRAW IN PADDY FIELDS (CASE IN MANDIKAPAU BARAT VILLAGE, BANJAR REGENCY, SOUTH KALIMANTAN) - Kadarsah, Anang; Komari, Noer; Prahatama Putra, Aminuddin; Sunardi; Eko Suhartono (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2023)
This study aims to determine the reasons for not using rice straw in the rice field landscape of Mandikapau Barat Village, Banjar Regency. Landscape ecology data extracted from Google Maps. Types, rice production, farmer profiles, and knowledge of rice straw utilization were identified through interviews. The relationship between profile and reasons for not using rice straw was determined by bivariate analysis. Results showed that fragments’ shape is generally elongated (70%) and others hexagonal (30%). The corridor in dry rice fields is 40-50 cm narrow, while in wet rice fields, the embankment width is about 60-80 cm. The average ownership of rainfed rice fields was about ±3,917.6 m2. From nine rice field fragments observed, the average area was ±14,788.4 m2. The most widely grown local rice varieties are Siam Pandak Laut and Siam Cantik. The local rice production rate reached ±2.6 Ton Ha-1, while rice straw production was ±3.6 Ton Ha-1. Most respondents are women (76%), smallholders (80%), and aged 40-50 years (48%). Most respondents (84%) stated rice straw could not be used and had been passed down from generation to generation (64%). There was a relationship between gender and knowledge of straw utilization (p=0.036<0.050) and reasons for not using rice straw (p=0.021<0.050).